Discrimination and differentiation among human beings; on the basis of color and creed. Attempts to eliminate them and their consequences and Reasoned solution - Mufti Dilawar Khan; Dr. Hafiz Muhammad Hussain (jihat-ul-islam, 2022)
This is a summary of my book “The Hundred Slave and Jurists”. The issue of slavery has been debated among scholars for a long time. This book clearly describes what slavery is and what its concept in Islam and other nations was. It further describes how the slaves were treated at that time and how it is present in many other forms now a days. Only the name has changed however place and status are the same in some nations. All the pre-Islamic civilized nations divided mankind into two permanent classes, one free man and the other slaves, and all the social rights were reserved for free people. Slaves could not benefit from them. Such nations considered slaves the most degraded in society and they were treated with contempt. But Islam protected the rights of the slaves and enforced it in practice. Books by historians and biographers are proof of this.